Cognitive Psychology as A Solution for Integrating Computational Thinking in Mathematics Education - Nikmah, Nafidatun; Suwito, Abi; Susanto; Musbikhin (Prodi. Manajemen Pendidikan Islam, Fakultas Tarbiyah, Institut Pesantren Sunan Drajat, 2025)
Integrating computational thinking skills into mathematics education poses a particular challenge, especially for students with cognitive barriers or learning difficulties. This study aims to examine relevant strategies for addressing the challenges of integrating computational thinking into mathematics learning through a cognitive psychology approach. Employing a literature review method, the research explores a variety of scholarly sources that discuss factors contributing to learning difficulties, both internal (such as cognitive and neurobiological development) and external (such as instructional design and teaching methods). The findings indicate that a cognitive psychological approach can be an effective solution, as it emphasizes thinking processes, motivation, and emotion in learning. Teachers must design instructional strategies that are responsive to students' cognitive capacities and support the development of computational thinking components, including problem decomposition, abstraction, pattern recognition, procedural algorithms, and generalization. With appropriate interventions, mathematics learning can shift its focus beyond content mastery to the sustainable development of computational thinking skills.